COPD patients with chronic bronchitis and higher sputum eosinophil counts show increased type‐2 and PDE4 gene expression in sputum. Issue 2 (9th December 2020) - Singh, Dave; Bassi, Michele; Balzano, Deborah; Lucci, Germano; Emirova, Aida; Anna Nandeuil, Marie; Jellema, Gera; Afolabi, Ebenezer K.; Leaker, Brian; Kornmann, Oliver; Michael Beeh, Kai; Watz, Henrik; et al.
Abstract: Chronic obstructive pulmonary disease (COPD) patients with higher eosinophil counts are associated with increased clinical response to phosphodiesterase‐4‐inhibitors (PDE4i). However, the underlying inflammatory mechanisms associated with this increased response is not yet elucidated. This post hoc analysis focused on sputum gene expression in patients with chronic bronchitis who underwent 32‐day treatment with two doses of the inhaled PDE4i CHF6001 (tanimilast) or placebo on top of triple therapy. Biological characterization and treatment effects were assessed between patients with different sputum eosinophil levels (eosinophil high  ≥ 3%; eosinophil low  < 3%) at baseline (primary samples) or at the end of the treatment of the placebo arm (validation samples). Forty‐one genes were differentially expressed in primary samples (p‐adjusted for false discovery rate < 0.05); all up‐regulated in eosinophil high patients and functionally enriched for type‐2 and PDE4 inflammatory processes. Eleven out of nineteen genes having immune system biological processes annotations including IL5RA, ALOX15, IL1RL1, CLC, GATA1 and PDE4D were replicated using validation samples. The expression of a number of these inflammatory mediators was reduced by tanimilast treatment, with greater effects observed in eosinophil high patients. These findings suggest that type‐2 and PDE4 overexpression in COPD patients with higher sputum eosinophil counts contribute to the differential clinical response to PDE4i observed in previous clinical trials.